[ y (Same)
Returns noun y unchanged: [y is equivalent to y.
z=: i.6 NB. try any noun here assert z -: [z
NOTE: Same (]) is equivalent to monadic [ when used monadically.
See Same (]), which is conventionally the one used in this role.
x [ y (Left)
Returns the (noun) value of x.
x=: 3 y=: 5 x [ y 3 assert x -: x [ y NB. try with any 2 nouns as x and y
1. Separate two assignments on the same line
The right-hand phrase must evaluate to a noun, to represent a valid y.
p=: 3 [ q=: 5
2. Separate two (numeric) atoms to prevent J treating them as a single noun (list).
z=: 1!:1 1 |rank error | z=: 1!:1 1 z=: 1!:1 [ 1 NB. read text from keyboard qwertyuiop
3. In a tacit phrase: bring in the value of argument x
13 : 'x+(x-y)*y' [ + - * ]